Unified fuzzy logic controller and power management for an isolated residential hybrid PV/diesel/battery energy system. Issue 4 (20th August 2022) - Atoui, Adil; Seghir Boucherit, Mohamed; Benmansour, Khelifa; Barkat, Said; Djerioui, Ali; Houari, Azeddine
Abstract: Hybrid systems based on renewable energies for the electrification of remote sites controlled by power management systems (PMSs) aim to reduce fossil fuels and increase the efficiency of renewable energy sources to minimize greenhouse gas emissions. The influential role of the PMS contributes to improving the efficiency and effectiveness of these systems by ensuring a balance between the different sources and loads in all operating modes. However, the abrupt transitions between the various operational modes selected by the PMS generate power loss and imbalance. To handle this issue, a fuzzy logic controller (FLC)-based PMS controlling a photovoltaic (PV) and diesel hybrid system with a battery storage element connected to a DC bus is proposed in this paper. The proposed PMS is wholly based on FLC to ensure a smooth transition between the different modes of the system. The success of using the suggested PMS lies in how well the FLC parameters are chosen before the system is processed. For this purpose, the particle swarm optimization algorithm is adapted to tune the FLC parameters. The resulting optimal intelligent PMS is tested and compared with a classical one using comprehensive simulations performed in a Simscape Electrical TM MATLAB® environment. The obtained results show an overshoot attenuation at the DC-bus voltage of 2% when changing the mode and an improvement in the PV generator efficiency by 99.5%. Graphical Abstract: